Principles of Sonar Performance Modelling - Ainslie, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Dr Ainslie$1 (Bs book provides a long-awaited complete and modern treatment of sonar performance modelling (SPM). In this context, the word "sonar" is used in a broad sense, to mean any deliberate use of underwater sound, including by marine mammals. The acronym "SONAR" stands for "sound navigation and ranging", but this book demonstrates how sonar systems and methodology are used for a variety of sensing, communications and deterrence systems, and by a number of industries and end-users (military, offshore, fisheries, surveyors and oceanography). The first three chapters provide background information and introduce the sonar equations. The author then lays the main foundations with separate chapters on acoustical oceanography, underwater acoustics, signal processing and statistical detection theory. These disparate disciplines are integrated expertly and authoritatively into a coherent whole, with as much detail as necessary added for more advanced applications of SPM. The book is illustrated with numerous worked examples, at both introductory and advanced levels, created using a variety of modern SPM tools.s
FOUNDATIONS -- Essential background -- The sonar equations -- THE FOUR PILLARS -- Sonar oceanography -- Underwater acoustics -- Sonar signal processing -- Statistical detection theory -- TOWARDS APPLICATIONS -- Sources and scatterers of sound -- Propagation of underwater sound -- Transmitter and receiver characteristics -- The sonar equations revisited.
Keywords: Geography; Physical geography; Oceanography; Acoustics; Environmental sciences; Earth Sciences; Geophysics/Geodesy.; Oceanography; Acoustics; Environment, general